Perancangan Aplikasi J2me Untuk Point Reward - Jaka Hartanto (ComTech: Computer, Mathematics and Engineering Applications, 2010)
As the development of communication technology, celular phone was no longer functioned as communication media but also as business media. This improvement could also be utilized as alternative of marketing strategy, one of it was point reward system which aimed to increase customer retention. The methology that would be used i.e. analitical analisys, literature and application design that of designing J2ME application to interact with customer. In analysis phase, several activities were: questionnaire which was spread to customer, interviewed the tenant and observed current marketing and promotion system in a mall. Information needed then analyzed as input. The input later be used in design phase to obtain the finals result in accordance with the requirements.